Weevil resistant sweetpotato through biotechnology - International Potato Center (2013)
Biotechnology has been applied to introduce synthetic genes that produce proteins with activity against the weevils. Out of about 30 transgenic events, one with the Cry3Ca1 gene displayed reduced infection and damages by weevils in a confined field trial in Puerto Rico. New gene constructs expected to result in enhanced accumulation of weevil-active proteins are now being used to transform sweetpotato varieties. As a complementary strategy, an RNAi strategy started with transcriptome analysis to identify weevil target genes. As this brief goes to press, !rst toxicity assays are currently underway on weevil larvae.